Physiological and Morphological Characteristics of Several Rice Varieties (Oryza sativa L.) In the System of Rice Intensification (SRI) Cultivation using Different Numbers of Seeds - Desi Ariani; Laila Nazirah; Baidhawi; Hafifah; Nilahayati (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Rice (Oryza sativa L.) is a vital food crop that serves as the staple food for over half of the world's population due to its rich nutritional value. This study aims to determine the physiological and morphological characteristics of several rice varieties cultivated using the System of Rice Intensification (SRI) with varying seed densities. The research will be conducted in Geulumpang Payong Village, Jeumpa District, Bireuen Regency, situated at an altitude of approximately 0-969 meters above sea level (masl), from August to December 2024. The study will employ a Randomized Block Design (RBD) methodology. Two factors will be tested: rice varieties (Ciherang, Inpari 49, and Mustajab) and the number of seedlings per planting hole (4, 3, 2, and 1 seedling). A total of 12 treatments were conducted, with each treatment replicated three times, resulting in 36 experimental units. Each experimental plot measured 2 m x 2 m, with a planting distance of 25 cm x 25 cm, accommodating 81 plants per plot. Four sample plants were selected from each plot for analysis. The data obtained from the research were statistically analyzed using the F-test with SAS V9.12 software. If the analysis of variance indicated significant differences at the 5% level, a subsequent Duncan's Multiple Range Test (DMRT) was performed. The results suggested that the variety, number of seedlings, and their interaction did not show significant differences across all parameters. However, the Inpari 49 and Mustajab varieties, along with the treatment of four seedlings per planting hole, demonstrated relatively favorable outcomes.